Cognitive Status In Thalassemia (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background: Thalassemia is one of the most common chronic and genetic hematological disorder. This chronic disease challenges the individual at the physical, emotional, cognitive level and disrupts the quality of life because of persistent anemia and hypoxia. The aim of study is to assess the cognitive status in thalassemia.Material and methods: This is a cross-sectional observational type of study that was performed in Autism and Child Development Center of Chattagram Maa Shishu–O–General Hospital. Children aged 6 to 16 years with thalassemia of different catagories were enrolled as study subjects. Study period was six months. Cognitive status of this study subject was assessed by WICS-IV equipment.Results: Among the 50 study subjects, Hb E b thalassemia was the most common type of thalassemia 39(78%). 2(4%) patient took oral chelating agent, 18 (36%) were under injectable, 20(40%) were found taking both oral and injectable and 10(20%) were observed not under any iron chelation therapy. Regular iron chelation therapy was found in 22(44%) cases.10(20%) cases had normal intelligence,19(38%) cases had mild mental retardation and 21 (42%) had moderate mental retardation. Among the 10 patients who do not use any chelation therapy,8(80%) patients had moderate retardation and 2(20%) had mild mental retardation. On the other hand, among the 40 patients who were having iron chelation therapy, 10(25%) patients showed normal level of intelligence, 17(42.5%) had mild mental retardation and 13(32.5%) had moderate mental retardation. In different score of WISC-IV, it was found that working memory and processing speed were poorer than verbal comprehension and perceptual reasoning in different type of thalassemia. This study also showed poor cognition is more prominent in thalassemia major and Hb E beta thalassemia.Conclusion: Cognitive status of the study subjects who take regular iron chelation therapy is much better than those who do not take iron chelation therapy. Hence, iron chelation therapy is proved to have better cognitive outcome for thalassemia patients with iron overload.Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 57-61